THE EVOLUTION OF POLITENESS: A HISTORICAL ANALYSIS OF ENGLISH NOVELS (Scientific journal of the Fergana State University, 2024)
This study examines the changing depiction of politeness in English novels from the 18th century to the present day, focusing on the portrayal of women and men. Through a historical analysis, it reveals a significant shift in the representation of politeness over time, reflecting changes in societal attitudes towards gender roles and relationships [10]. The study argues that the portrayal of politeness has become more nuanced and egalitarian over time, reflecting a growing recognition of the importance of equality and respect in relationships between women and men [13]. The analysis shows that the portrayal of politeness has evolved from a patriarchal paradigm in the 18th and 19th centuries, to a more complex and egalitarian representation in the 20th century, and finally to a dynamic process that involves mutual respect, empathy, and understanding in contemporary English novels. Overall, the study highlights the importance of politeness in relationships between women and men and its evolution over time.